Predatory Exclusive Dealing - Joachim Klein; Hans Zenger (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2009)
While the previous literature on exclusive dealing has been concerned with the question of how exclusive dealing can raise static profits, this paper analyzes the question of how exclusive dealing can be used to predate in a dynamic context. It is shown that exclusive dealing may arise even if it reduces static profits. Exclusivity provisions may not only allow excluding efficient competitors, but indeed are often a cheaper exclusionary tool than predatory pricing. This is the case if the prey's access to finance is not too limited. Furthermore, it is more likely that exclusive dealing is preferable compared to predatory pricing the more market power the predator has with respect to the prey.
urn:nbn:de:bvb:19-epub-10626-0
Keywords: K21; L11; L12; L41; L42; 330; exclusive dealing; predation; Vertriebsbindung; Verdrängungswettbewerb; Spieltheorie; Theorie